“Efecto de diferentes niveles de cal y de humus de lombriz en el rendimiento de maíz (zea mays) en un suelo ácido del sector San Juan- Banda de Shilcayo, Provincia de San Martín” - Celis Escudero, Manuel Armando (2003)
The present work of thesis developed in the sector La Florida, Distrait of the Band Shilcayo, Province and Region San Martin, characterized for presenting a climate of tropical humid forest (bh -T) 1 250 mm/year, 605 mm. During experiment, into purpose to study the effect of interaction lime/humus at increase of maize production, to correct pH of soil (Recovery of Acid Soils) and carry out economical analysis of treatments established. The éultivation used was maize, variety Marginal 28 Tropical, installed in a design of plots divided inside a Random Complete Block design, corresponding to plots the different levels ofLime and Sub-Plots to the levels oftime Humus. The experiment did realize in a land with moderate slope into equivalent 8.08% with Secondary forest (Punna) where the soil classifies as Ultisol, the color of soil is yellowish, without presence of stones not rocks. From the results obtained deduce that yields of Maize increase with reduction of soil acidity improving its pH through in corporation of lime, reaching to produce for different treatments: Tl3 = 1,558.04 Kg/Ha. T14 = 1,566.53 Kg/Ha. Tl5 = 1,570.50 Kg/Ha. T16 = 1,578.83 Kg/Ha. To value an the rendition of the Testifier, this obtain 939.56 KgiHa (O TM Lime/ O TM Humus). The economical analysis reported a rentability of 0.31, 0.34 and 0.25 (Tl6, T12 and T8) for the culture production cost of treatments Lime/Humus with relation of Testifier (TI).